University Choice: The Role of Expected Earnings, Nonpecuniary Outcomes, and Financial Constraints - Delavande, Adeline; Zafar, Basit (Journal of Political Economy, 2019)
We investigate the determinants of students’ university choice in Pakistan, with a focus on monetary returns, nonpecuniary factors enjoyed at school, and financial constraints. To mitigate the identification problem concerning the separation of preferences, expectations, and market constraints, we use rich data on subjective expectations, with direct measures of financial constraints, to estimate a life-cycle model of school choice jointly with school-specific expectations of dropping out. We find that labor market prospects play a small role. Instead, nonpecuniary outcomes, such as the school’s ideology, are the major determinants. Policy simulations suggest that relaxing financial constraints would have large welfare gains.